La desorganización familiar y su incidencia en el desarrollo educativo de los niños de la escuela Lauro Damerval Ayora nº 2; y la intervención del (a) trabajador(a) social. - Chamba Capa, Rosa Victorina (2012)
The present investigation work is titled "THE FAMILY DISORGANIZATION AND ITS INCIDENCE IN THE EDUCATIONAL DEVELOPMENT OF THE CHILDREN OF THE SCHOOL "LAUREL DAMERVAL AYORA Nº 2; And THE (TO) SOCIAL" WORKER'S (TO) INTERVENTION, for their execution, methodology of scientific investigation was used, aided among other in the inductive, deductive, descriptive methods; and in the same way in the field investigation were applied technical as the observation and survey, so much to the family parents like the students; all this sustained in a vast bibliography that you/they allowed to obtain fundamental approaches for the correct development of the same one. In the field investigation, it could settle down that 60% of the students of the establishment is of masculine sex, and 40% they belong to the feminine sex; he/she also settled down that 45% of the students lives with its mother and its father and 35% they only live with its mother, 20% of the students doesn't have this luck for what you/they are different relatives who have taken the responsibility of taking care of them; according to 20% of the students its home is disorganized any communication type since it doesn't exist and problems always exist especially for the abandonment of one of the parents; he/she was also proven that for 60% of those interviewed the communication is simply regular, what gives us the rule that this it is an aspect that has certain weakness inside the family, what could explain that 55% of the adolescents affirms to have had problems at some time inside the family circle. We could also check that the yield of the youths in 45% is to regulate, what allows to deduce that the family difficulties influence in form negative in the academic yield of the youths. As for the approach of the family parents, their 70%, he/she affirms that in their homes if manifestations of family disorganization have been given, 100% of the family parents, he/she affirms that the family disorganization harms the educational development of the children. Likewise the educational ones interviewed, they affirm that so much the infidelity, migration divorces, they are all the causes so that you of the family disintegration, influencing negatively in the educational development of the children. The statistical tabulation and graphic representation of the obtained data, and once discussed and analyzed these, you could end up defining the conclusions and to present recommendations, jointly with a proposal to give solution to the problem.